Serologic characteristics of hepatitis B virus among hill-tribe children in Omkoi district, Chiangmai province, Thailand - Khamduang, Woottichai; Ponchomcheun, Nichagamon; Yaaupala, Witchuda; Puwaruengpat, Phongpatchara; Hongjaisee, Sayamon; Samleerat, Tanawan; Yanola, Jintana; Pornprasert, Sakorn; Ratanasthien, Kwanchai; Jourdain, Gonzague; Ngo-Giang-Huong, Nicole; Sirirungsi, Wasna (The Journal of Infection in Developing Countries, 2019)
Introduction: Thailand has integrated hepatitis B (HB) vaccination of newborns into the national Expanded Program on Immunization (EPI) in 1992. This has led to a dramatic decrease of HBsAg prevalence in children. However, HB vaccine coverage in remote areas is not well-known. This study aimed to investigate serologic characteristics of hepatitis B virus (HBV) among hill-tribe children in Omkoi District, Chiangmai Province, Thailand. Methodology: This cross-sectional study was conducted on stored samples collected from hill-tribe children attending the primary/secondary school in Omkoi District in December 2014. Sera were tested for HBsAg, anti-HBs and anti-HBc using enzyme immunoassays (MUREX, DiaSorin, Italy). Samples with anti-HBc positive were further assessed for HBV DNA using an in-house HBV DNA semi-nested polymerase chain reaction (PCR) assay. Results: Of 210 children evaluated, 4 (1.9%:95% CI 0.5-4.8) were HBsAg-positive. Of the 206 children HBsAg negative, 17 were anti-HBc and anti-HBs positive, 15 anti-HBc positive only, 26 anti-HBs positive only and 148 negative for both anti-HBc and anti-HBs. None of the children with anti-HBc were positive for HBV DNA. Conclusions: A high percentage of children had no markers of HBV protection suggesting that HB vaccine coverage was not optimal in this area. Our results warrant HBV serologic investigations in other remote areas to assess whether HB vaccine coverage needs to be improved and to identify children who should be vaccinated.